How to develop debating skills from the class of Philosophy? - Lidia Cira Carbonell Izquierdo; Juan Alberto Blanco Rivera (Revista MENDIVE, 2003)
This article addresses the issue Learning Developer. Based on the use of a system of teaching methods, posed by a group of researchers from ICCP. It is the collaboration of professors of philosophy to respond from our modest experiences difficulties showing our students with the skills to develop political debates in our institution.